Antiphospholipid Antibodies in Women with Recurrent Urinary Tract Infection - khoshroo, mohammad; Azad, Ali Reza; Zolfaghari, Mohammad Reza (Archives of Medical Laboratory Sciences, 2020)
Background: A variety of infections, including acute and recurrent urinary tract infections (UTIs), can trigger production of antiphospholipid antibodies (aPL). These antibodies in women can lead to recurrent pregnancy loss. The aim of this study was to evaluate the prevalence of aPL in recurrent UTI patients. Materials and Methods: A total 52 subjects who had positive urine culture and 50 healthy individuals as controls were evaluated for presence of lupus anticoagulant (LA), anticardiolipin, anti-β2 GPI(anti-